Sperm viability percentage by flow cytometry during the cryopreservation process in spermatozoa obtained from alpaca epididymis - Juárez, Javier (2019)
The aim of this study was to determine the percentage of viability in alpaca epididymal spermatozoa before and after the cryopreservation process by flow cytometry. A total of 46 alpaca testes were collected from a slaughterhouse in Pasco, Peru and 41 of them were used with sperm motility ≥30% and sperm concentration ≥50x106 sperm/ml. Spermatozoa were recovered from the tail of the epididymis with 1 ml of skimmed milk-based extender, separating into two aliquots to evaluate viability before and after the cryopreservation process. The extender was removed by washing by centrifugation with PBS, the pellets were resuspended in 100 μl of PBS, adding 0.5 μl of SYBR-14 (100 nM) and 0.5 μl of propidium iodide - PI (12 μM), and incubated for 10 min at 38 °C. The evaluation of sperm viability was performed by flow cytometry with image analyzer, using an excitation laser of 488 nm and the fluorescence emitted by SYBR-14 and PI were detected by channels Ch02 (505-560 nm) and Ch05 (642-740 nm), respectively. Viable spermatozoa with intact membrane emitted green fluorescence (SYBR-14) and non-viable sperm with damaged membrane emitted red fluorescence (PI). The viability before the cryopreservation process (48.97 ± 11.47%) was higher (p<0.05) than after the cryopreservation process (32.30 ± 9.57%). The correlation between viability and sperm motility was r=0.6737. It is concluded that the cryopreservation process significantly reduces the viability in alpaca epididymal spermatozoa, and viability is related to sperm motility.